Revisión inicial de la literatura sobre la formación de profesores de ciencias naturales desde un enfoque STEAMH en educación secundaria (Memorias Sifored - Encuentros Educación UAN, 2022)
The STEAMH methodology has aroused the interest of the academic community in recent years due to the impact it can have on educational processes. However, there has been little training of methodologies with this approach, which generates a limited implementation in the didactic and methodological practices of science teachers. Therefore, the present work has made a bibliographic review and the results show that there is a great interest on the part of the research community in finding relationships between the teaching of sciences, engineering and the arts as an integrative strategy. Teacher training with a STEAMH approach has difficulties when it comes to being implemented due to the lack of coordination between the domain of knowledge and the way of considering integrality. Nevertheless, it is considered to be a permanent need and requires constant innovation processes.
Keywords: Teacher Training; methodology; STEAMH; Natural Sciences; Education